ANALISIS PERUBAHAN BENTUK CHASIS TERHADAP BEBAN SEBAGAI DASAR PERANCANGAN MESIN BENDING HIDRAULIC - Makinun, Makinun; Anggono, Agus Dwi; Riyadi, Tri Widodo Besar (Jurnal Rekayasa Mesin, 2024)
In the world of the automotive industry there are still several problems that must be resolved, such as what happened in one of the workshops, there was a shortage of tools to repair bent truck frames because of the accident. One of the tools needed to repair the frame is the bending tool, with this the planning process for making the tool has a problem with the ability of the hydraulic tool to be used to repair the frame of the Mitsubishi Center 125. With the simulation method using SolidWorks software, it can be seen that the force load on the frame of the Mitsubishi center 125 will then obtain data that can be analyzed using the finite element method. In the simulation, try to use a force load of 1 ton.f to 20 ton.f at two points, namely the center and side, then can be seen that the displacement of the object that occurs. The results of the simulation are increasing the force load, the degree of change in shape is increasing along with the damage to the object and the highest change of 500 mm so it requires the ability of hydraulic tools that have a compressive capacity of more than 20 tons.